2010
DOI: 10.1021/ja1018783
|View full text |Cite
|
Sign up to set email alerts
|

Organic n-Channel Field-Effect Transistors Based on Arylenediimide-Thiophene Derivatives

Abstract: The synthesis, structural, electrochemical, and thin film electrical and electronic structural properties of a series of arylene diimide-oligothiophene n-type semiconductors are reported. This family of compounds allows analysis of the effects on thin film transistor performance of the following: (i) oligothiophene backbone catenation; (ii) naphthalenediimide vs perylenediimide core interchange; (iii) phenylene group introduction in the oligothiophene backbone. Electrochemical experiments indicate similar redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 120 publications
9
126
0
1
Order By: Relevance
“…Furthermore, molecular tailoring of organic compounds via chemical modification can achieve high field-effect performance of the active semiconducting layers. For example, fused acene [18], oligothiophene [19], tetrathiafulvalene derivatives [20] and conjugated polymers [21] exhibit field-effect mobilities much larger than 0.1 cm 2 V −1 s −1 . However, the chemical and electrical stabilities of these OFETs, and consequent degradation in on-current, threshold voltage and field-effect mobility under air exposure remain a problem.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, molecular tailoring of organic compounds via chemical modification can achieve high field-effect performance of the active semiconducting layers. For example, fused acene [18], oligothiophene [19], tetrathiafulvalene derivatives [20] and conjugated polymers [21] exhibit field-effect mobilities much larger than 0.1 cm 2 V −1 s −1 . However, the chemical and electrical stabilities of these OFETs, and consequent degradation in on-current, threshold voltage and field-effect mobility under air exposure remain a problem.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Especially remarkable has been the investigation on different oligothiophenes covalently linked to naphthalimides, [4][5][6] the smallest member of the rylene colorant family, 7,8 because of their significance as organic materials and in supramolecular chemistry. 9 Thus, in the last few years we have synthesized oligothiophene-naphthalimide and peryleneimide assemblies ( Figure 1a) with good performances in organic field-effect transistors (OFETs) 10,11 in which both donor and acceptor moieties are directly conjugated through either imidazole or pyrazine rigid linkers. It was found that the absence of skeletal distortions allows closer intermolecular π-π stacking and enhances intramolecular π-conjugation, thus promoting good film crystallinity and low reorganization energies for both electron and hole transport.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, X-Ray diffraction of single crystal of some of our previously synthesized derivatives of these families (Figure 1) show that the conjugated D-A molecules stack with neighboring molecules packing in a head-totail fashion. This should not be in principle a problem for photoelectric conversion and charge transport, 10 if the frontier molecular orbitals were delocalized over the whole conjugated skeleton. 16 However, in systems closely related with these semiconductors, 10,12 we have demonstrated that the HOMO and LUMO levels are localized on the oligothiophene and arylene fragments, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of solubilizing groups on highly conjugated backbone is usually accompanied by unintended and unfavorable change in molecular-packing pattern by distorting the molecular backbone or by steric hindrance of huge substituents, which results in limited device performance [20][21][22][23][24][28][29][30][31]. Therefore, it is highly desirable to make OTFTs with small molecular organic semiconductors without any molecular modification nor performance decrease using some simple wet-processes.…”
Section: Introductionmentioning
confidence: 99%